Teacher’s Motives in Applying Communication Accommodation Strategies in Secondary ELT Class - Almas Rizkika Nabila; Ahmad Munir; Syafi’ul Anam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The objective of this study is to describe teacher’s motives that underlie the use of communication accommodation strategies in secondary ELT class. This study employed a qualitative approach by observing the strategies used in ELT class and interviewing teacher to ask the reason for performing those features. The participant of this study was one English teacher from secondary ELT class. The result showed that teacher used more convergence features in accommodative strategies rather than divergence. Besides, teacher’s motives in applying communication accommodation strategies were categorized as affective motives to emphasize the closeness with students and cognitive motives to improve students’ understanding in classroom interaction. Teacher was dominant in cognitive motives rather than affective motives when using communication accommodation strategies in secondary ELT class. Keywords: Communication Accommodation Strategies, Affective Motives, Cognitive Motives